Analysis and Evaluation of User Acceptance on the Use of Enterprise Resource Planning (ERP) Systems at PT Trisco Tailored Apparel Manufacturing - Alma Syafira; Warih Puspitasari; Wahjoe Witjaksono (IJAIT (International Journal of Applied Information Technology), 2021)
Enterprise Resource Planning is a system that connects business areas, which benefits companies by increasing productivity, reducing costs, and simplifying business processes. However, it also found a case that considers the use of ERP systems to fail. Therefore, the use of ERP systems needs to be optimized, one of which is in terms of users. This research will be analyzed and evaluated the factors that influence user acceptance using the TAM2 model. The variables used are 11 variables in TAM2, including moderator variables. This research was conducted at PT Trisco Tailored Apparel Manufacturing, with a sample of 43 and an online questionnaire as a data collection method. Data processing using SmartPLS. The analysis conducted in the analysis of inner models such as validity and reliability tests, and analysis of inner models such as the coefficient of determination and path coefficient. The final step is testing the hypothesis with the bootstrapping method. The results obtained are the most significant factor is the image of the perceived usefulness, then the perceived usefulness of the intention to use the system. It has also found that if the system were mandatory, voluntariness would not be significant. Therefore, the results of this study can use as a source of evaluation for the company.